Management : an organizational perspective - Gannon, Martin J. (Boston : Little, Brown and Co., 1977)
This book attempts to develop a model of management that integrates the two streams of thought in this field, economics and behavioural science, and the major schools within each stream. In addition, as the title implies, it views management as the complex set of activities by which managers establish, maintain, and improve successful organizations.
Includes index.
Includes bibliographical references: p. 445-455.
ne 10/02/2020
Loans
Keywords: Management; Organization